2013
DOI: 10.1016/j.clinph.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Mapping repetition suppression of the P50 evoked response to the human cerebral cortex

Abstract: Objective-The cerebral network subserving repetition suppression (RS) of the P50 auditory evoked response as observed using paired-identical-stimulus (S1-S2) paradigms is not welldescribed Methods-We analyzed S1-S2 data from electrodes placed on the cortices of 64 epilepsy patients. We identified regions with maximal amplitude responses to S1 (i.e., stimulus registration), regions with maximal suppression of responses to S2 relative to S1 (i.e., RS), and regions with no or minimal RS 30-80ms post stimulation.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 62 publications
2
34
0
Order By: Relevance
“…In apparent contrast to the sparse interconnection between (auditory) temporal cortex and STN, frontal cortical areas have intimate relations with the STN (Monakow et al, 1978;Nambu et al, 1996;Haynes and Haber, 2013). Interestingly, the inferior frontal cortex-a candidate target structure for functional STN-DBS effects (Aron and Poldrack, 2006)-exhibits maximal gating of P1 (Boutros et al, 2013) and N1 (Boutros et al, 2011), respectively. Taking this anatomical information into consideration, it may be postulated that STN-DBS exerts an influence on sensory gating functions of the frontal cortex-either through modulation of pallido-thalamic output or through retrograde Table 2 Results of repeated measures ANOVA for effects of treatment on peak-to-peak amplitudes.…”
Section: Downstream Effects Of Stn-dbsmentioning
confidence: 90%
See 1 more Smart Citation
“…In apparent contrast to the sparse interconnection between (auditory) temporal cortex and STN, frontal cortical areas have intimate relations with the STN (Monakow et al, 1978;Nambu et al, 1996;Haynes and Haber, 2013). Interestingly, the inferior frontal cortex-a candidate target structure for functional STN-DBS effects (Aron and Poldrack, 2006)-exhibits maximal gating of P1 (Boutros et al, 2013) and N1 (Boutros et al, 2011), respectively. Taking this anatomical information into consideration, it may be postulated that STN-DBS exerts an influence on sensory gating functions of the frontal cortex-either through modulation of pallido-thalamic output or through retrograde Table 2 Results of repeated measures ANOVA for effects of treatment on peak-to-peak amplitudes.…”
Section: Downstream Effects Of Stn-dbsmentioning
confidence: 90%
“…It is of note that a number of studies investigating the neural circuitry involved in auditory sensory gating (i.e., tempo-dependent P1/N1 suppression) converge on demonstrating a prominent involvement of the prefrontal cortex (Knight et al, 1989;Weisser et al, 2001;Grunwald et al, 2003;Korzyukov et al, 2007;Garcia-Rill et al, 2008;Mayer et al, 2009;Boutros et al, 2011;Boutros et al, 2013). In apparent contrast to the sparse interconnection between (auditory) temporal cortex and STN, frontal cortical areas have intimate relations with the STN (Monakow et al, 1978;Nambu et al, 1996;Haynes and Haber, 2013).…”
Section: Downstream Effects Of Stn-dbsmentioning
confidence: 93%
“…Repeating the same acoustic stimulus within sufficiently short time-intervals (typically between 0.5-2.0 s) significantly attenuates the AEPs associated with the second stimuli. This phenomenon, which is known as auditory gating is impaired in various neurological and psychiatric disorders, has attracted considerable interest over the past two decades, since it has been recognized as an endophenotype of CNS disorders and been also utilized in genetic studies (Boutros et al, 2013;Hajós, 2006;Hong et al, 2008;Thaker, 2008). Using clinically equivalent acousticstimulation paradigms, auditory-gating phenomena have been observed in experimental animals, which could be disrupted by pharmacological, environmental or genetic manipulations to model sensory-gating deficits of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In humans however, intracranial recordings have revealed that hippocampal engagement occurs approximately 200 milliseconds post-stimulus and therefore, although not directly related to P50 generation (Grunwald et al, 2003), instead may suppress P50 generators activated by the second click (Korzyukov et al, 2007). Also implicated in sensory gating are generators in the frontal lobe (Korzyukov et al, 2007;Weisser et al, 2001), superior temporal gyrus (Thoma et al, 2005), prefrontal cortex (Grunwald et al, 2003), and cingulate and parietal lobe regions (Boutros et al, 2013), along with multiple neurotransmitter systems including GABAergic, cholinergic, dopaminergic, serotonergic and glutamatergic systems (Adler et al, 1998). Relevant to the current study and as noted earlier, THC is thought to disrupt the regulatory action of the endocannabinoid system on these neurotransmitter systems (Lopez-Moreno et al, 2008;Mathur and Lovinger, 2012).…”
Section: Introductionmentioning
confidence: 99%